Beyond the Call - Belic, Adrian (Belic, Adrian, 2006)
Verzio FF submission In an Indiana Jones meets Mother Teresa adventure, three middle-aged men – former soldiers and modern-day knights – travel the world delivering life-saving humanitarian aid directly into the hands of civilians and doctors; in some of the most dangerous yet beautiful places on Earth, the front lines of war.